524p75NTR-dependent activation of NF-kB is required for the trafficking and transcriptional regulation of microRNA-503 in microvascular complications of diabetes. (15th July 2014) - Caporali, A; Meloni, M; Mitic, T; Nailor, A; Emanueli, C
Abstract: Purpose: Uncontrolled hyperglycemia is responsible for vascular complications in diabetes. Together with pericytes, endothelial cells (ECs) establish direct cell-to-cell communication in the blood vessel that is fundamental for the regulation of microvascular formation, stabilisation and function. Notably, circulating microparicles (MPs) can serve as signalling molecules and mediators of inter-cellular communication. Recently, we also demonstrated that in ECs microRNA-503 (miR-503) and neurotrophin receptor p75 (p75NTR) individually facilitate diabetes-induced impairment of EC function. This study investigated how expression of miR-503 and its release are regulated by p75NTR in diabetes, and what role do miR-503-carrying microparticles (MPs-miR-503) play in communication between EC and vascular pericytes. Methods: Type 1 diabetes was induced in mice by injection of streptozotocin. Mice underwent unilateral limb ischemia followed by gene transfer using adenoviral vectors. Blood flow recovery was monitored by laser Doppler and post-ischemic angiogenesis was assessed by immunostaining.  ECs were cultured in high glucose and reduced of growth factors to mimic diabetes and ischemia. Binding of NF-kB to miR-503 promoter was verified by chromatin immunoprecipitation. MPs were prepared by centrifugation and validated by flow cytometric analysis as events with 0.1-1mm diameter expressing Annexin V. To study the trafficking between ECs and pericytes, an in vitro co-culture system was used, along with an ex-vivo model from diabetic limb muscles. Results: Our findings show that expression of miR-503 and p75NTR increase in ECs in vitro, due to high glucose, as well as in diabetes with ischemia in vivo. Modulation of p75NTR expression regulates transcription of miR-503 and consequently EC function and post-ischemic angiogenesis. We provide evidence that p75NTR promotes activation of NF-kB in ECs, which binds the promoter of miR-503 thus upregulating its expression. NF-kB further induces the shedding of MPs-miR-503 from the ECs, through activation of Rho kinase (ROCK). Circulating MPs-miR-503 are engulfed by vascular pericytes in a RAGE (receptor for advance glycation end product)-dependent manner. This reduces the expression of miR-503 targets like ephrinB2 (EFNB2) and vascular endothelial growth factor-A (VEGFA), and causes functional impairments in pericytes. Conclusion: Here we describe a newly-established mechanism for regulation and release of miRNA-503 into MPs during diabetes-induced vascular diseases.